Prospects for the use of waste from the processing of hydrobionts - Levkivska, Tetiana; Matko, Svitlana; Benderska, Olha (Problems of Environmental Biotechnology, 2021)
The directions of utilization of waste of hydrobionts - an important task for owners of the enterprises which are engaged in the trade of fish, crustaceans and mollusks or production from them of products are considered.